1979
DOI: 10.1002/1097-0142(197907)44:1<215::aid-cncr2820440135>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hyalinizing granulomas in a patient with malignant lymphoma, with development nine years later of multiple myeloma and systemic amyloidosis

Abstract: In our patient, multiple bilateral nodular pulmonary densities appeared on a chest x-ray at the time of diagnosis of stage IV diffuse lymphocytic lymphoma. After localized radiation therapy, the patient received no further systemic therapy. The pulmonary nodules slowly became larger and more numerous. Nine years later the patient developed proven multiple myeloma. Pulmonary hyalinizing granulomas have not heretofore been associated with proven lymphoreticular neoplasia, although this has long been suspected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…PHG was associated with an infection in 19 cases (14.1 %). Tuberculosis was the most common (n= 14) 2,7,9,30,36,48,50,65,69,72,73,74 . One case of infection with the Human Immunodeficiency virus (HIV) was reported in association with PHG 65 .…”
Section: Pathological Conditions Associated With Phgmentioning
confidence: 99%
See 1 more Smart Citation
“…PHG was associated with an infection in 19 cases (14.1 %). Tuberculosis was the most common (n= 14) 2,7,9,30,36,48,50,65,69,72,73,74 . One case of infection with the Human Immunodeficiency virus (HIV) was reported in association with PHG 65 .…”
Section: Pathological Conditions Associated With Phgmentioning
confidence: 99%
“…PHG was associated with an hematological disease in 5 cases (3.7 %): amyloidosis (n=2) 2,25 , multiple myeloma, lymphoma and amyloidosis (n=1) 7 , MALT lymphoma (n=1) 36 and Castleman's disease (n=1) 27 .…”
Section: Pathological Conditions Associated With Phgmentioning
confidence: 99%
“…The occurrence of small cell-type malignant disease, specifically lymphoma in this condition, has long been postulated, but only one case with PHG associated with stage IV diffuse lymphocytic lymphoma of the abdomen has been reported. 5 We present the first case of PHG and concomitant low-grade small lymphocytic B lymphoma of the lung.…”
mentioning
confidence: 97%
“…Since the first report by Engleman et al 1 in 1977, to the best of our knowledge, 61 cases of PHG have been reported in the English-language literature. [2][3][4][5][6][7] The nodules are typically benign in histology and clinical course, but slowly grow in size and number. Because of their behavior and to rule out a malignancy, biopsy is required to establish the primary diagnosis of PHG.…”
mentioning
confidence: 99%
“…This view is supported by findings in many other reports stating that myeloma was followed by an excess of NHL and leukemia. 1,4,[13][14][15][16][17][18][19][20] Standard incidence ratio for NHL after myeloma is 1.74 according some studies. 1 Morover, Onishi H et al, 26 reported a patient who developed NHL in remission of MM after 12 yr long treatment.…”
Section: Discussionmentioning
confidence: 99%